Clinical Management of Molar Incisor Hypomineralization Affected Molars in a Pediatric Patient Including Endodontic Treatment, Case Report and Review of the Literature - Alfarraj JH; Alsaeed AA (Dove Medical Press, 2022)
Jawza H Alfarraj,1 AbdulAziz A Alsaeed2 1Pediatric Dentistry, King Fahad Medical City, Riyadh, Saudi Arabia; 2Endodontics, King Abdul-Aziz Medical City, Riyadh, Saudi ArabiaCorrespondence: Jawza H Alfarraj, Tel +966 509948859, Email Jawza500@gmail.comAbstract: The term molar incisor hypomineralization (MIH) describes the clinical manifestation of enamel hypomineralization of systemic origin affecting one or more permanent first molars and incisors. The purpose of this case report is to discuss the management of two mandibular molars with hypomineralization and to emphasize endodontic treatment for pediatric patients. An 8-year-old girl was referred to the pediatric dental clinic for restorations of multiple carious teeth. Upon clinical examination, based on the pattern of enamel hypomineralization and posteruptive breakdown presented, the diagnosis of MIH was established. As a part of the comprehensive treatment, one molar was restored with resin-based composite restorations. The other was endodontically involved and was treated with apexification and then covered with a stainless-steel crown. A two-year recall appointment revealed both molars to be free from signs and symptoms of inflammation. Management of MIH-affected molars should follow a conservative approach and endodontic treatment should be considered.Keywords: case report, molar incisor hypomineralization, MIH, apexification, mineral trioxide aggregate, pediatric dentistry